2020
DOI: 10.7150/ijms.37626
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Usefulness of Predictive Models for Preterm Birth with Potential Benefits: A KOrean Preterm collaboratE Network (KOPEN) Registry-Linked Data-Based Cohort Study

Abstract: Background: Preterm birth is strongly associated with increasing mortality, incidence of disability, intensity of neonatal care required, and consequent costs. We examined the clinical utility of the potential preterm birth risk factors from admitted pregnant women with symptomatic preterm labor and developed prediction models to obtain information for prolonging pregnancies. Methods: This retrospective study included pregnant women registered with the KOrean Preterm collaboratE Network (KOPEN) who had symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 33 publications
2
21
0
2
Order By: Relevance
“…However, PTB aetiology remains not fully understood. Despite the multitude of risk factors identified 6 , the majority of preterm births do not have a specific risk factor. Several different pathological processes have been implicated in preterm birth, including ischemia, stress, infections, cervical diseases and other 7 .…”
Section: Introductionmentioning
confidence: 99%
“…However, PTB aetiology remains not fully understood. Despite the multitude of risk factors identified 6 , the majority of preterm births do not have a specific risk factor. Several different pathological processes have been implicated in preterm birth, including ischemia, stress, infections, cervical diseases and other 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Obstetric care providers have conventionally depended on clinical symptoms such as pelvic pressure and regular uterine contraction to identify women at risk of PTB (7). Recent studies have shown that reliance on clinical symptoms alone is unreliable and inaccurate (8). Clinical reports also posit several risk factors for PTB including genetic influence/family history of previous PTB (9), poor nutrition (10), cervical insufficiency accompanied by secondary premature cervical shortening (11), infection (12,13), and tobacco intake (14).…”
mentioning
confidence: 99%
“…Although this modification was adequate, it did not report sensitivity, specificity, or negative- or positive-predictive values. Nomograms have also been developed and validated to predict PTB clinically (Allouche et al, 2011; Lee et al, 2020). One nomogram was proposed by the KOrean Preterm collaboratE Network (KOPEN) and was used to calculate risk probability.…”
mentioning
confidence: 99%